Game technologies as a means of increasing the educational motivation of university students - Tsyganova, Larisa V. (2020)
Game technologies allow bringing the educational process as close as possible to professional activities, activating the cognitive interest of students in the study of professional disciplines. The purpose of the article is to analyze the experience of implementing gaming technologies in the preparation of students of higher educational institutions to increase their motivation for learning. Game technologies are a set of methods and techniques for organizing the educational process in the form of various games that stimulate cognitive activity. They allow you to simulate a real workflow and consolidate theoretical material. Motivation is defined as a set of internal motivations that explain the student’s behavior, orientation and activity in the educational process. Motivation acts as a continuous choice and decision-making based on weighing behavioral alternatives. The article presents a study of the impact of gaming technology on changing students' motivation. As a tool for the study of motivation, we used Dubovitskaya methodology for the diagnosis of motivation. The study reflects the impact of gaming technology on changing student motivation. The implementation of gaming technologies in the training of students of a higher educational institution helps to increase the motivation of students to study professional disciplines, the formation of professional competence.